2001
DOI: 10.1159/000049165
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Cancer Refractory to Chemotherapy: A Role for Octreotide?

Abstract: Although octreotide has been shown to inhibit the growth of gastrointestinal (GI) tumors in vitro and in vivo, preliminary clinical trials have reported disappointing results for this somatostatin analog in patients with GI cancers. The results of these trials probably reflect the difficulty in assessing the therapeutic potential of an agent such as octreotide in GI cancers. Thus, it is possible that treatment with octreotide could be useful in the stabilization of disease if it is associated with an improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The diverse results of the studies found in literature may be caused by methodological alterations and clinical differences [58]. Among the five known somatostatin receptors primarily SSTR2 and SSTR5 mediate the antiproliferative effect of SST and its analogues.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse results of the studies found in literature may be caused by methodological alterations and clinical differences [58]. Among the five known somatostatin receptors primarily SSTR2 and SSTR5 mediate the antiproliferative effect of SST and its analogues.…”
Section: Discussionmentioning
confidence: 99%
“…subcutaneously (s.c.) for 2 months lowered serum IGF-I, caused major side effects such as cramps, but had no effect on tumors [189]. Cascinu et al [190] reviewed these clinical studies and concluded that the results available suggest that octreotide is not effective in the management of untreated patients with advanced GI cancer, but additional studies of octreotide in chemotherapy-resistant patients are needed [190]. Avastin (bevacizumab), a recombinant monoclonal antibody targeting VEGF, is in a phase III clinical trial in patients with advanced colon cancer.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The overall results indicate that treatment with octreotide and other octapeptide analogs of somatostatin is not effective in patients with advanced pancreatic cancer [192]. Cascinu et al [190] concluded that although the results of clinical trials suggest that octreotide is not effective in untreated patients with advanced pancreatic cancer, additional details are needed to evaluate octreotide in chemotherapy refractory patients in order to clarify its effects not only on the survival, but also on the quality of life of the patients [190].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…As discussed by Cascinu et al [83] in another paper in this volume, there is an urgent need for large controlled trials to evaluate the efficacy of adjuvant therapies after surgery. Somatostatin analog therapy may, as discussed earlier for colorectal and pancreatic cancer, be a valuable treatment for gastric cancer to potentiate the effects of chemotherapy and via their stimulatory effect on hepatic RES activity inhibit the growth and development of liver metastases.…”
Section: Gastric Cancermentioning
confidence: 99%